A Focus Group Discussion on the Beneﬁts of Bio-pigment in Preventing Stunting and Obesity with RPTRA Administrators in South Jakarta - Naurissa Biasini; Reni Dyanasari; Fitriyah Nurhidayah; Pratika Riris Putrianti; Leenawaty Limantara (Direktorat Pengabdian kepada Masyarakat Universitas Gadjah Mada, 2022)
The problem of stunting in Indonesia has recently been getting worse and has become in the top three positions in Southeast Asia due to the lack of public understanding, one of which is about nutrition. Currently in Jakarta, to reach mothers, RPTRA (Ruang Publik Terpadu Ramah Anak/Child-friendly Integrated Public Space) administrators can assist in providing information about nutrition, especially those that can overcome the problem of stunting more broadly. This activity was carried out to provide more understanding of stunting prevention nutrition for RPTRA administrators. After receiving seminar and workshop materials, a Focus Group Discussion was held for RPTRA administrators regarding the beneﬁts of biopigments in preventing Stunting and Obesity. Each group was given a question related to their knowledge of changes about biopigments beneﬁts in fruits and vegetables. FGD data was analysed by using three methods of coding (open, axial, and selective coding). Eighty per cent of the answers from RPTRA administrators were still limited to sources of nutrition that were commonly used on a daily basis, even though their level of understanding about nutritional sources had increased after the seminars and workshops. The main reason for this was because there was still a view that other sources of nutrition that they had just discovered were considered expensive or diﬃcult to ﬁnd.